Pengaruh Perilaku Keuangan, Latar Belakang Bisnis Keluarga, Tingkat Pendidikan, dan Sosialisasi Keuangan terhadap Literasi Keuangan UMKM di Gunungkidul - Seliana Intan Tri; Rizal Rinofah; Alfiatul Maulida (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the effect of financial behavior, family business background, education level, and MSME financial socialization in the Wonosari District, Gunungkidul. The research method uses quantitative. The population in this study were UKM in Wonosari, Gunungkidul Regency. The sample of this research is small MSMEs in Wonosari Gunungkidul Regency and has a minimum number of employees of 5 people. The sampling technique used purposive sampling with the slovin formula with a standard error of 10% so that a total sample of 72 business actors was obtained. The analysis tool used for testing is SmartPls ver.4. The results showed that all variables, namely financial behavior, family business background, level of education and financial socialization, had a significant positive effect on the financial literacy of MSMEs in the Wonosari District, Gunungkidul.